PENGARUH DISIPLIN KERJA MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT SARI WARNA ASLI UNIT V KUDUS (Studi Kasus pada Karyawan bagian Produksi) - Kiki Lestari; Agung Budiatmo (Universitas Diponegoro, 2018)
The purpose of this study is to determine the effect of work discipline, work motivation and work environment on the performance of employees of production PT Sari Warna Asli Unit V Kudus. The type of research using explanatory research with data collection methods using interviews and data collection tools using questionnaires with a sample of 82 respondents employees of the production of PT. Sari Warna Asli Unit V Kudus uses Probability Sampling method. The analysis technique used validity test, reliability test, simple linear regression, multiple linear regression, t test, and F test with SPSS 16.0. From result of research indicate that work discipline have strong influence to employee performance equal to 75%, work motivation have good effect to employee performance equal to 63% and work environment have good effect to employee performance equal to 65,4% while simultan work discipline, work motivation and work environment strong influence on employee performance of 79,6%. This means that the better the discipline of work, work motivation and work environment then the higher the performance of employees of the production of PT. Sari Warna Asli Unit V Kudus. Job discipline variable to employee performance variable has the greatest influence from work motivation variable and work environment. Based on the results of the study, researchers suggested that PT. Native Color Sari further impose strict sanctions on employees who do not comply with company regulations, pay more attention to security and comfort employees in working for better performance